Advanced Electrocatalysts for Low-Temperature Fuel Cells (Springer International Publishing, 2018)
This book introduces the reader to the state of the art in nanostructured anode and cathode electrocatalysts for low-temperature acid and alkaline fuel cells. It explores the electrocatalysis of anode (oxidation of organic molecules) and cathode (oxygen reduction) reactions. It also offers insights into metal-carbon interactions, correlating them with the catalytic activity of the electrochemical reactions. The book explores the electrocatalytic behaviour of materials based on noble metals and their alloys, as well as metal-metal oxides and metal-free nanostructures. It also discusses the surface and structural modification of carbon supports to enhance the catalytic activity of electrocatalysts for fuel-cell reactions.